Tandem repeat expansions and copy number variations as risk factors and diagnostic tools for amyotrophic lateral sclerosis - Sabetta, Eleonora; Ferrari, Davide; Massimo, Locatelli; Kõks, Sulev (Frontiers in Neurology, 2025)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder leading to upper and lower motoneurons degeneration. Although several mechanisms potentially involved in disease development have been identified, its pathogenesis is not fully understood. From the patient side, ALS diagnosis, still based on clinical criteria, can be difficult and may take up to 1 year. More than 30 genes have been associated to genetically inherited ALS, among which four (C9ORF72, SOD1, TARDBP and FUS) would explain around 60–70% of cases. However, familial ALS represents only 5–10% of ALS cases while the remaining are sporadic, with genetics explaining 6–10% of such cases only. In this context, short tandem repeats (STRs) expansions, have recently been found in clinically diagnosed ALS patients. In this review, we discuss the recent discoveries on ALS associated STRs and their potential as biomarkers as well as prognosis and therapy targets.